(untitled) (MAUSAM, 2024)
The availability and assimilation of INSAT-3D and INSAT-3DR weather satellite datasets has improved the accuracy of medium range weather forecasts. Conventionally, the forecast is verified against the in-situ observations. But the distribution of in-situ observatories is not uniform for many reasons like, in-habitable conditions, mountain terrains, operational cost etc. The availability of data from Automatic weather stations is also not guaranteed at all times because of maintenance and operational issues. Therefore, in the absence of in-situ data it becomes very difficult to verify the forecast. In the current study, skill of value added rainfall forecast is assessed by carrying out skill score analysis for Assandh (AS), Gharaunda (GD), Indri (ID), Karnal (KA), Nilokheri (NK) blocks using in-situ rain-gauge data for the southwest monsoon season of 2020 and 2021. For Munak (MU), Kunjpura (KJ) and Nissing (NI) blocks, the data from rain-gauges is not available. In order to fill this gap, in the present study, the block level medium-range value added rainfall forecast issued by IMD, is verified by utilizing INSAT-3DR satellite Hydro-estimator (HE) rainfall product. In order to gain confidence in the approach, the INSAT-3DR derived HE rainfall estimate is validated against the available rain-gauges in Karnal district. The study revealed that the rainfall data received from the satellite can be used for better forecasting of daily rainfall at the block level and preparation of agromet advisory bulletin. The accuracy of forecast of weather parameters in advance is found to be useful for farmers for doing appropriate field operations and crop management practices in the form of preparation of Agromet Advisories Bulletin (AAB).